2019
DOI: 10.5194/acp-19-5511-2019
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale transport into the Arctic: the roles of the midlatitude jet and the Hadley Cell

Abstract: Abstract. Transport from the Northern Hemisphere (NH) midlatitudes to the Arctic plays a crucial role in determining the abundance of trace gases and aerosols that are important to Arctic climate via impacts on radiation and chemistry. Here we examine this transport using an idealized tracer with a fixed lifetime and predominantly midlatitude land-based sources in models participating in the Chemistry Climate Model Initiative (CCMI). We show that there is a 25 %–45 % difference in the Arctic concentrations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…We consider all models in each project and do not separate free‐running or specified dynamics models. (Note, Orbe et al, , ; and Yang, Waugh, Orbe, et al, , have shown that the spread in transport among specified dynamics models is comparable to that for free‐running models in CCMI.) There are small differences in the SF 6 emissions used between the TransCom and CCMI models (TransCom models used EDGAR v4.0, whereas CCMI models used EDGAR v4.2), but the τ ex and SF 6 age calculations are not sensitive to these differences as both calculations are more dependent on meridional gradient of SF 6 concentrations and not on emissions.…”
Section: Methodsmentioning
confidence: 94%
“…We consider all models in each project and do not separate free‐running or specified dynamics models. (Note, Orbe et al, , ; and Yang, Waugh, Orbe, et al, , have shown that the spread in transport among specified dynamics models is comparable to that for free‐running models in CCMI.) There are small differences in the SF 6 emissions used between the TransCom and CCMI models (TransCom models used EDGAR v4.0, whereas CCMI models used EDGAR v4.2), but the τ ex and SF 6 age calculations are not sensitive to these differences as both calculations are more dependent on meridional gradient of SF 6 concentrations and not on emissions.…”
Section: Methodsmentioning
confidence: 94%
“…All tracers decay uniformly at a loss rate of τ = 50 days −1 . Tracers with the same loss have been used in prior studies (e.g., Orbe et al, 2017Orbe et al, , 2018Shindell et al, 2008;Yang et al, 2019). Although not the primary focus of our analysis, we also explore how the lifetime of tracers impacts their relationship with the jet by simulating χ 40−50 with loss rates of τ = 5, 25, 100 and 150 days −1 .…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore important to know the processes controlling this transport and how the transport will change with climate. Previous studies comparing simulations of real and idealized tracers show a large spread among models (Monks et al., 2015; Orbe et al., 2017, 2018; Shindell et al., 2008; Yang et al., 2019). Furthermore, there remain large uncertainties in the role of different processes in causing changes, such as the relative role of changes in the large‐scale circulation, isentropic mixing, and convection (e.g., Orbe et al., 2018; Yang et al., 2019).…”
Section: Introductionmentioning
confidence: 98%